Multipolar Intuitionistic Fuzzy Positive Implicative Ideal in B-Algebras - Royyan Amigo; Noor Hidayat; Vira Hari Krisnawati (Cauchy: Jurnal Matematika Murni dan Aplikasi)
In this paper, we start with the concept of B-algebras, commutative B-algebras and fuzzy ideal in B-algebras. We also study about multipolar intuitionistic fuzzy ideal. We explain the notion of multipolar intuitionistic fuzzy positive implicative ideal in B-algebras and some characterizes. In addition, we examine some theorems and proportions which contain the conditions for a multipolar intuitionistic fuzzy set become a multipolar intuitionistic fuzzy positive implicative ideal in B-algebras. One of the result is a multipolar intuitionistic fuzzy set (l,s) over commutative B-algebra X is a multipolar intuitionistic fuzzy positive implicative ideal (l,s) over commutative B-algebra X if and only if (x*y)*z=0 implies l(x)= Inf{l(y),l(z)} and s(x) = Sup{s(y),s(z)}, for all x,y,z.